The Influence of Leadership Style, Career Development and Compensation on Organizational Citizenship Behavior of Civil Servants in The Sub-District City of Payakumbuh - Ikhsani Novella; Syamsir Syamsir (Program Pascasarjana Universitas Negeri Makassar, 2023)
This study aims to provide evidence that: 1) To analyze the effect of leadership style on the Organizational Citizenship Behavior of Sub-District Civil Servants in Payakumbuh City. 2) To analyze the effect of career development on the Organizational Citizenship Behavior of Sub-District civil servants in Payakumbuh City. 3) To analyze the effect of compensation on the Organizational Citizenship Behavior of Sub-District Civil Servants in Payakumbuh City. 4) To analyze the effect of leadership style, career development and compensation simultaneously on the Organizational Citizenship Behavior of Sub-District Civil Servants in Payakumbuh City. The population in this study were all District Government Civil Servants in the City of Payakumbuh, totalling 290 employees. The sampling technique in this study used a proportional random sampling technique with a specified number of samples of 169 respondents. Data collection was carried out using a survey method with a questionnaire. The data analysis technique used in this research is descriptive and quantitative analysis. The data collected is primary and secondary, which can be classified as independent and dependent variables. Testing the hypothesis in this study using multiple linear regression tests. Based on the study's results, it is known that 1) Leadership style has a positive and partially significant effect on the Organizational Citizenship Behavior of Sub-District Civil Servants in Payakumbuh City where Tcount is greater than Ttable where 3.500> 1.974 with a significance of 0.001 <0.05. 2) Career development has a positive and significant partial effect on the Organizational Citizenship Behavior of Sub-District Civil Servants in Payakumbuh City, where Tcount is greater than Ttable where 3.242>1.974 with a significance of 0.000<0.05. 3) Compensation has a positive and significant partial effect on the Organizational Citizenship Behavior of Sub-District Civil Servants in Payakumbuh City, where Tcount is greater than Ttable where 2.692>1.974 with a significance of 0.000<0.05. 4) Leadership style, career development and compensation positively and significantly affect the Organizational Citizenship Behavior of Sub-District Civil Servants in Payakumbuh City.